Extreme time–frequency connectedness between oil shocks and sectoral markets in the United States - Oguzhan Ozcelebi; Jose Pérez-Montiel; Sang Hoon Kang (Financial Innovation)
Abstract This study assessed the connectedness between oil shocks and industry stock indexes in the United States (US). We consider the normal and extreme conditions across different frequency horizons, and the quantile time–frequency connectedness method is used to determine the tail risk contagion under different frequency horizons. Our results reveal that the short-term frequency connectedness significantly exceeds the long-term frequency connectedness. We also indicate that the connectedness in the lower and upper quantiles is greater than at the conditional mean. Importantly, oil risk shock is the biggest net transmitter of shocks to the US sectors in normal and extreme conditions, highlighting that oil risk shocks cause substantial variations in US sector stock returns in the short, medium, and long term. Finally, QAR(3) model demonstrates the significant impact of oil risk shocks on US sector stock returns during extreme and normal conditions. Therefore, our study underscores the role of asymmetry in the reaction of US sector stock returns to oil-related shocks, and we suggest that policies aimed at overcoming the adverse effects of oil shocks on stock markets and promoting financial stability should incorporate asymmetric features.